Clinical case: a foreign body of the esophagus under the mask of an intestinal infection - Elena V. Melekhina (LLC "MEDIAFORMAT", 2023)
The authors present an analysis of a clinical case of a patient who was taken to the children's infectious diseases department of Khimki regional Hospital with suspected acute intestinal infection of unclear etiology and transferred to another hospital after establishing the non-core nature of the disease. The article presents the most informative clinical symptoms and anamnestic data in the differential diagnosis of intestinal infection with acute pathology - aspiration of a foreign body into the esophagus. To remove the foreign body, the patient was taken to the thoracic department of the St. Vladimir children's city clinical Hospital, where esophagoscopy was performed. despite the relatively large size of the aspirated object, it was possible to remove it without complications through the natural respiratory tract.